Novel Betaherpesviruses in Neotropical Bats on the Caribbean Island of St. Kitts: First Report from Antillean Tree Bats (Ardops nichollsi) and Evidence for Cross-Species Transmission - Jessica L. Kulberg; Sarah Hooper; Yashpal S. Malik; Souvik Ghosh (Microorganisms)
To date, limited information is available on herpesviruses in bats from the Caribbean region. We report here high detection rates (24.24%, n = 66) of herpesviruses in oral samples from apparently healthy bats (Ardops nichollsi (75%, 9/12) and Molossus molossus (28%, 7/25)) on the Lesser Antillean Island of St. Kitts. Based on analysis of partial DNA polymerase (DPOL) sequences (~225 amino acid (aa) residues), we identified two distinct groups of herpesviruses (BO-I and -II) that were unique to A. nichollsi and M. molossus, respectively. Within the subfamily Betaherpesvirinae, the BO-I DPOL sequences shared low deduced aa identities (<70%) with other herpesviruses, and phylogenetically, they formed a distinct cluster, representing a putative novel betaherpesvirus. The BO-II DPOL sequences were closely related to a putative novel betaherpesvirus from a M. molossus in Lesser Antillean Island of Martinique, indicating possible transmission of herpesviruses by bat movement between the Caribbean Islands. Phylogenetically, the BO-I and -II betaherpesviruses exhibited species-specific (A. nichollsi and M. molossus, respectively) as well as family-specific (Phyllostomidae and Molossidae, respectively) clustering patterns, corroborating the hypothesis on host specificity of betaherpesviruses. Interestingly, a single M. molossus betaherpesvirus strain clustered with the A. nichollsi betaherpesviruses, indicating possible interspecies transmission of herpesviruses between Phyllostomidae and Molossidae. To our knowledge, this is the first report on detection of herpesviruses from Antillean tree bats (A. nichollsi), expanding the host range of betaherpesviruses. Taken together, the present study identified putative novel betaherpesviruses that might be unique to chiropteran species (A. nichollsi and M. molossus), indicating virus–host coevolution, and provided evidence for interspecies transmission of betaherpesviruses between chiropteran families.